Determinants of Continued Use of Agile Methods: A Case Study of an E-Commerce Enabler in Indonesia - Prisillia, Galuh; Raharjo , Teguh; Trisnawaty, Ni Wayan (SAFE-Network, 2025)
Agile methodologies have gained popularity for their adaptability, faster time-to-market, and enhanced customer satisfaction. However, sustaining their use post-adoption poses challenges, including knowledge gaps, resistance to change, and communication issues. This study examines the determinants of continued use of Agile methods at PT XYZ, an e-commerce enabler in Indonesia. Using the Expectation Confirmation Model and Partial Least Squares Structural Equation Modeling, data from 61 IT staff members were analyzed to evaluate relationships between Confirmation, Perceived Usefulness, Satisfaction, and Continuance Intention. Results reveal that CO positively impacts PU and SA, while PU and SA significantly influence CI. Satisfaction emerges as a critical mediator between perceived value and continued use. These findings highlight the importance of aligning Agile practices with user expectations and perceived benefits to ensure sustained adoption. Practical implications include the need for comprehensive training, regular evaluations of team satisfaction, and organizational alignment with Agile principles.